Perceptions of academicians at Academy of Islamic Studies on library services: A preliminary study - Noorsuzila, M.; Sinnasamy, J. (2015)
Purpose: This paper describes a user survey carried out at Academy of Islamic Studies, University of Malaya as an initiative to communicate with library users.